2022
DOI: 10.1002/app.52362
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol)/modified cassava starch blends plasticized with glycerol and sorbitol

Abstract: A series of blend films comprised 88% hydrolyzed poly(vinyl alcohol) (PVA) with native cassava starch (NCS), high‐oxidized cassava starch (HCS), and pre‐gelatinized cassava starch (PCS) was prepared via solution casting. The blends were plasticized with glycerol or glycerol‐sorbitol mixture. The structure of each blend film was characterized by Fourier‐transform infrared spectroscopy and X‐ray diffraction analysis. Cross‐sections of the PVA/HCS and PVA/PCS blend films, imaged by scanning electron microscopy, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…The findings suggested that a higher degree of oxidation led to a reduction in moisture absorption due to an increase in carbonyl/carboxyl groups and a decrease in hydroxyl groups. 44 Additionally, an increased degree of oxidation was associated with elevated decomposition temperatures. In comparison, native starch underwent decomposition at 317.8 °C, while oxidized starches decomposed at 322.7 °C (10 wt% NaCl, 12 V, 30 min), 319 °C (15 wt% NaCl, 24 V, 30 min), and 318 °C (15 wt% NaCl, 24 V, 120 min).…”
Section: Resultsmentioning
confidence: 99%
“…The findings suggested that a higher degree of oxidation led to a reduction in moisture absorption due to an increase in carbonyl/carboxyl groups and a decrease in hydroxyl groups. 44 Additionally, an increased degree of oxidation was associated with elevated decomposition temperatures. In comparison, native starch underwent decomposition at 317.8 °C, while oxidized starches decomposed at 322.7 °C (10 wt% NaCl, 12 V, 30 min), 319 °C (15 wt% NaCl, 24 V, 30 min), and 318 °C (15 wt% NaCl, 24 V, 120 min).…”
Section: Resultsmentioning
confidence: 99%
“…O alto grau de intumescimento dos filmes da blenda resultou em rápida degradação no solo após apenas 4 dias. Também foram identificados uma série de filmes que mostraram maior resistência e alongamento na ruptura do que a baixa densidade do polietileno, sugerindo que essas misturas são ambientalmente benignas e candidatas ideais para aplicações generalizadas em produtos derivados do petróleo (Boonsuk, et al, 2022).…”
Section: Discussionunclassified
“…Among all the biopolymers, PVA/starch blends have been studied owing to the availability and affordability of the starting materials [18–20]. Often, crosslinking agents, plasticizers and reinforcing agents are added as additives along with ultrasonic or radiation treatments in order to further enhance the physical and chemical properties and applicability of the starch–PVA films [21, 22]. Introduction of crosslinking agents and plasticizers into the polymer matrix is convenient and effective in reducing the intermolecular forces between macromolecular chains, which improves the flexibility, mechanical properties and water resistance of the starch–PVA films.…”
Section: Introductionmentioning
confidence: 99%